Review: Pemanfaatan Tape Kentan sebagai Sumber Energi Alternatif Berbasis Pangan Fermentasi untuk Beberapa Daerah di Indonesia - Siti Dwi Cahira; Ardi Mustakim (CV. Muara Edukasi, 2026)
Indonesia’s dependence on fossil energy sources remains high, while their availability continues to decline and contributes to increasing carbon emissions and environmental degradation. This condition encourages the development of alternative energy sources that are renewable, environmentally friendly, and based on local potential. One underexplored potential is tape kentan, a traditional fermented food product produced through microbial activity capable of generating energy. Tape kentan contains simple carbohydrates resulting from the fermentation process that can potentially be converted into alternative energy, particularly bioethanol. This study aims to comprehensively review the utilization of tape kentan as an alternative energy source based on fermented food in several regions of Indonesia. The research method employed is a literature review, examining scientific sources such as national and international journals, research reports, and relevant publications discussing food fermentation and alternative energy. The results indicate that tape kentan has a relatively high reducing sugar content due to the activity of yeast and bacteria during fermentation, making it a potential raw material for bioenergy production. The utilization of tape kentan as an alternative energy source is considered suitable for rural areas with abundant local raw materials. These findings suggest that traditional fermented foods have not only consumption value but also strategic value in supporting energy security. In conclusion, tape kentan has the potential to be developed as a local wisdom-based alternative energy source with further research support and appropriate policies